Examination of Coach and Player Perceptions of Recovery and Exertion. Issue 5 (May 2020) - Kraft, Justin A.; Laurent, Matthew C.; Green, James M.; Helm, Jessica; Roberts, Cooper; Holt, Swan
Abstract : Abstract: Kraft, JA, Laurent, ML, Green, JM, Helm, J, Roberts, C, and Holt, S. Examination of coach and player perceptions of recovery and exertion. J Strength Cond Res 34(5): 1383–1391, 2020—Monitoring training and recovery are essential for exercise programming. Athletes can validly assess training load (TL) via the session rating of perceived exertion (SRPE) technique. However, it is unclear if coaches can successfully use this model. This study compared coach and athlete perceptions of effort and recovery, and it evaluated the efficacy of perceptually based TL monitoring. Participants included 56 athletes (Women's volleyball, soccer, and basketball and Men's basketball) and their coaches ( n = 4). Perceived recovery was estimated via the Perceived Recovery Status scale. Scores of TL were calculated using the Edward's heart rate (HR) method and by multiplying SRPE by duration. Coaches provided an intended SRPE (SRPE-CI) before practice. Also, SRPE was independently estimated by coaches (SRPE-CO) and athletes (SRPE-A) ∼15–20 minutes after practice. Paired t -tests and Pearson's correlations were applied to make comparisons (α ⩽ 0.05). Values of SRPE-CI, SRPE-CO, SRPE-A TLs were strongly correlated with Edwards' HR-based TLs ( R = 0.74, 0.73, and 0.76, respectively). However, SRPE-CI (5.5 ± 1.9) and SRPE-CO (5.0 ± 1.9) was higher than SRPE-A (4.5 ± 1.9). Coaches estimated recovery higher than athletes (7.1 ± 1.3 vs. 5.8 ± 1.6). Estimates of TL strongly correlated with Edwards' TL regardless of information source (coach or athlete) or time point (SRPE-CI TL or SRPE-CO TL). Results suggest that coaches' perceptions validly indicated TL. Coaches' perceptions provide parallel information (correlated strongly with Edwards TL) but not identical information (demonstrated by differences in SRPE) as athlete perceptions. Differences in perceived recovery indicate that coaches overestimate recovery when compared with athletes' perceptions.